2022
DOI: 10.3390/children9050680
|View full text |Cite
|
Sign up to set email alerts
|

Socioemotional Skills Program with a Group of Socioeconomically Disadvantaged Young Adolescents: Impacts on Self-Concept and Emotional and Behavioral Problems

Abstract: There is significant evidence that emphasizes the importance of social and emotional learning in schools for students’ positive development and adjustment. The main goal of the present study was to evaluate the effectiveness of a socioemotional skills promotion program, implemented with a group of socioculturally vulnerable young adolescents. Data were collected in the 2020–2021 school year from all students from 6th grade (n = 50, from four classes) in a high-risk school in Portugal (56% females). Two classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
3
2
0
1
Order By: Relevance
“…Social awareness increased after the intervention for kindergarten, lower-secondary and higher secondary students. These results are consistent with previous studies showing a positive impact of SEL programs on socio-emotional skills [ 23 ]. Specifically, existing research showed the efficacy of SEL programs in enhancing SEL competencies for kindergarten children [ 46 ], primary school students [ 45 ] secondary school students [ 47 ], and high school students [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Social awareness increased after the intervention for kindergarten, lower-secondary and higher secondary students. These results are consistent with previous studies showing a positive impact of SEL programs on socio-emotional skills [ 23 ]. Specifically, existing research showed the efficacy of SEL programs in enhancing SEL competencies for kindergarten children [ 46 ], primary school students [ 45 ] secondary school students [ 47 ], and high school students [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Analyzing the effect of school level, we found that after the intervention, internalizing, externalizing problems, and total difficulty decreased significantly in primary school students. Our results are in line with other studies that identified similar effects of SEL programs on internalizing and externalizing difficulties [ 22 , 23 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations